República, republicanismo e republicanos: Brasil, Portugal, Itália - Armando Malheiro da Silva (Documentos, 2011)
This book, edited by three historians, each focusing on a different country, began to be prepared in 2005, five years before the centenary of the Republic in Portugal, and not in any way inspired by that event in any way. However, a marked delay in putting the idea into practice meant that the edition was only launched in 2011.ALT_QUEBRA_LINHAThere were other reasons behind this. The idea was stimulated by the first Portugal, Brazil and Italy conference on themes and problems of political history and 20th century ideologies, which took place in November 2005 at the University of Bologna, one of the three universities involved (the other two are the University of Coimbra and the University of São Paulo). Connected to these institutions are research units and projects such as the Centre for 20th century Interdisciplinary Studies (CEIS 20, Coimbra, Portugal), the PROIN - Integrated State Archive Project/ University of São Paulo and the Dipartimento di Discipline Storiche della Universit